2020
DOI: 10.1039/c9nr07602f
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale, low-cost, broadband and tunable perfect optical absorber based on phase-change material

Abstract: We experimentally demonstrate a large-scale, low-cost, broadband, and tunable metamaterial absorber using phase change material. Based on two distinct resonance mechanisms, the device exhibits high absorptivity for both visible and near-IR lights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…Since Landy et al demonstrated the first metamaterial absorber with one perfect absorption peak in the microwave band through an experiment 19 , the control and engineering of the spectral absorption properties of MPAs has attracted significant interest. In their experiment, broadband perfect absorption was achieved with MPAs in microwave regime [20][21][22][23][24] and was extended from visible [25][26][27][28][29][30][31][32][33][34][35][36][37] , infrared [38][39][40][41][42][43][44][45][46][47][48][49][50][51] and THz [52][53][54][55][56][57] bands. This study will compare these representative theoretical and experimental works on the topic of broadband MPAs from visible to infrared bands in supplement document.…”
Section: Introductionmentioning
confidence: 98%
“…Since Landy et al demonstrated the first metamaterial absorber with one perfect absorption peak in the microwave band through an experiment 19 , the control and engineering of the spectral absorption properties of MPAs has attracted significant interest. In their experiment, broadband perfect absorption was achieved with MPAs in microwave regime [20][21][22][23][24] and was extended from visible [25][26][27][28][29][30][31][32][33][34][35][36][37] , infrared [38][39][40][41][42][43][44][45][46][47][48][49][50][51] and THz [52][53][54][55][56][57] bands. This study will compare these representative theoretical and experimental works on the topic of broadband MPAs from visible to infrared bands in supplement document.…”
Section: Introductionmentioning
confidence: 98%
“…However, a big problem is that the shifting the frequency can lead to a mismatch in impedance, which limits the adjustable range with high efficiency. Additionally, in most cases, the real part (n) and imaginary part (k) of the refractive index both change during the process, which further enlarges the mismatch and leads to a sharp drop in absorptivity during the tuning process [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The controllable methods of tunable metamaterials are included thermal control, [ 37,38 ] optical pumping, [ 39–41 ] and micro/nano‐electro‐mechanical system (M/NEMS) control [ 42–44 ] to enhance their flexibilities. These tunable mechanisms can also be combined with the extra functional materials such as phase change materials, [ 37,45,46 ] liquid crystal, [ 47 ] superconductors, [ 48,49 ] 2D materials, [ 50–52 ] and flexible materials [ 53 ] to tune the electromagnetic characterizations including resonant frequency, transmission amplitude, perfect absorption, free spectrum range (FSR), bandwidth, and so on. These can largely improve the practicability of metamaterials in the cloaking, superlens, subwavelength imaging, holography, perfect absorber, sensor, filter, all‐optical modulation, programmable logic operation, nonlinear optics, and so on.…”
Section: Introductionmentioning
confidence: 99%